2019
DOI: 10.1016/j.eurox.2018.100001
|View full text |Cite
|
Sign up to set email alerts
|

Examining the infectious aetiology and diagnostic criteria of maternal pyrexia in labour to improve antibiotic stewardship

Abstract: Objectives To determine the infectious aetiology of peripartum maternal pyrexia and to assess the diagnostic accuracy of obstetric systemic inflammatory response syndrome criteria and cardiotocography as predictors of peripartum infection, in order to guide appropriate antibiotic management of mother and neonate. Study Design This study was carried out in a tertiary referral maternity hospital in Dublin, Ireland. A prospective cohort analysis was performed of 175 mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…10,40,45 As a result, many patients for whom the sepsis bundle has been initiated may not have an infectious aetiology. Fitzgerald et al, 52 in a prospective study of 175 intrapartum women with pyrexia >38°C, showed that no patients developed sepsis or required admission to ICU. 52 They argue that de-escalation of antibiotics could be considered if sterile site cultures are negative at 48 hours and the patient is clinically well, 52 along the lines of current national guidance for the neonate.…”
Section: Controversiesmentioning
confidence: 99%
See 1 more Smart Citation
“…10,40,45 As a result, many patients for whom the sepsis bundle has been initiated may not have an infectious aetiology. Fitzgerald et al, 52 in a prospective study of 175 intrapartum women with pyrexia >38°C, showed that no patients developed sepsis or required admission to ICU. 52 They argue that de-escalation of antibiotics could be considered if sterile site cultures are negative at 48 hours and the patient is clinically well, 52 along the lines of current national guidance for the neonate.…”
Section: Controversiesmentioning
confidence: 99%
“…Fitzgerald et al, 52 in a prospective study of 175 intrapartum women with pyrexia >38°C, showed that no patients developed sepsis or required admission to ICU. 52 They argue that de-escalation of antibiotics could be considered if sterile site cultures are negative at 48 hours and the patient is clinically well, 52 along the lines of current national guidance for the neonate. 53 However, given the poor sensitivity/specificity of current microbiological culture techniques and in the absence of a more sensitive tool, de-escalation should be determined with microbiological guidance.…”
Section: Controversiesmentioning
confidence: 99%
“…Preterm birth after spontaneous labour with prolonged preterm rupture of membranes necessitated antibiotic use, meaning many premature babies receive antibiotics as default. Additionally, in practice a low threshold is used to manage maternal perinatal fever as sepsis 14 which obligated neonatal antibiotic prescribing. Clinical indicators of neonatal sepsis were non-specific, 1 based on low-quality evidence 2 and risked subjective interpretation.…”
Section: Original Researchmentioning
confidence: 99%